Peningkatan Aktivitas Dan Hasil Belajar Ipas Bagian Tubuh Tumbuhan Kelas IV Dengan Pendekatan Jelajah Alam Sekitar - Husaen Sudrajat; Risa Herlina Hariati; Nurin Kumala Dewi (STAI AL-AMIN, 2023)
Students' active involvement in the learning process is one indicator of the effectiveness of Independent Curriculum learning. Apart from that, students must also meet the learning outcome standards determined by the KKTP. However, at MI NW Gelogor, a problem was found in learning science and technology regarding plant body parts. Students look passive and do not participate much in learning. Apart from that, the KKTP analysis shows that only 33% of students succeeded in achieving learning completion. In overcoming the findings of this problem, the researcher attempted to carry out research to improve science learning with the aim of ensuring that student learning outcomes can meet completeness standards and increase student activity. This research was carried out using the PTK method which consists of Cycle I and Cycle II actions. In the learning process, this research applies a natural exploration approach. The research data source was obtained from 30 class IV students at MI NW Gelogor. Information regarding student activities and learning outcomes is collected through observation sheets, short fill-in tests, and documentation. The collected results are then analyzed qualitatively and quantitatively using percentages. The results of the research are conclusions which show an increase in learning activities in Cycle I and Cycle II actions.